The University of Alabama at Birmingham COVID‐19 Collaborative Outcomes Research Enterprise: Developing an institutional learning health system in response to the global pandemic - Jami L. Anderson; Rebecca A. Reamey; Emily B. Levitan; Irfan M.Asif; Monica S.Aswani; Faith E. Fletcher; Allyson G.Hall; Kierstin C. Kennedy; Dustin Long; David Redden; Alia Tunagur; Molly Wasko; et al. (Learning Health Systems, 2022)
Abstract Introduction As a local response to the COVID‐19 global pandemic, the University of Alabama at Birmingham (UAB) established the UAB COVID‐19 Collaborative Outcomes Research Enterprise (CORE), an institutional learning health system (LHS) to achieve an integrated health services outcomes and research response. Methods We developed a network of expertise and capabilities to rapidly develop and deploy an institutional‐level interdisciplinary LHS. Based upon a scoping review of the literature and the Knowledge to Action Framework, we adopted a LHS framework identifying contributors and components necessary to developing a system within and between the university academic and medical centers. We used social network analysis to examine the emergence of informal work patterns and diversified network capabilities based on the LHS framework. Results This experience report details three principal characteristics of the UAB COVID‐19 CORE LHS development: (a) identifying network contributors and components; (b) building the institutional network; and (c) diversifying network capabilities. Contributors and committees were identified from seven components of LHS: (a) collaborative and executive leadership committee, (b) research coordinating committee, (c) oversight and ethics committee, (d) thematic scientific working groups, (e) programmatic working groups, (f) informatics capabilities, and (g) patient advisory groups. Evolving from the topical interests of the initial CORE participants, scientific working groups emerged to support the learning system network. Programmatic working groups were charged with developing a comprehensive and mutually accessible COVID‐19 database. Discussion Our LHS framework allowed for effective integration of multiple academic and medical centers into a cohesive institutional‐level learning system. Network analysis indicated diversity of institutional disciplines, professional rank, and topical focus pertaining to COVID‐19, with each center leveraging existing institutional responsibilities to minimize gaps in network capabilities. Conclusion Incorporating an adapted LHS framework designed for academic medical centers served as a foundational resource supporting further institutional‐level efforts to develop agile and responsive learning networks.